Jejak-Jejak Pengutusan Musa Membebaskan Bangsa Israel Dari Perbudakan Mesir (Keluaran 6:1-12) - Nikodemus Nikodemus; Andreas Jimmy (Student Scientific Creativity Journal, 2023)
The focus of this paper is the theme of the Mission of Moses to Free the Israelites from Egyptian Slavery Exodus 6:1-12. The salvation of the Israelites is inseparable from the struggle of Moses who was blessed by God. But with God's word to Moses all problems were resolved with an outstretched hand. The purpose of this paper is to discover the location of God's role for the Israelites who were enslaved by Egypt at that time. The methodology used is the exegesis methodology. There are 6 analyzes used, namely analysis of Story, Structure, Syntax, Semantics, Context, and Theological Reflection. The six analyzes have been done on separate sheets and are summarized in this article. The findings obtained from this writing include: First, God's inclusion in Moses, who struggled with a lack of self-confidence. Second, God's inclusion appeared in Moses when Moses freed the Israelites from Egyptian slavery. Third, God always accompanies those who rely on God in their work. Thus Christians are invited to always rely on God in their life journey.